Intramural duodenal hematoma secondary to pancreatitis: case report and review of the literature - Oliveira, João Henrique Botto de (2018)
CONTEXT: Spontaneous intramural duodenal hematoma is uncommon and is usually associated with coagulopathy, anticoagulant therapy and endoscopic procedures. The aim here was to describe a case of intramural duodenal hematoma caused by chronic exacerbation of pancreatitis. CASE REPORT: A 46-year-old male with chronic alcoholic pancreatitis was admitted to hospital due to abdominal pain, melena and low hemoglobin. An intramural duodenal hematoma with active bleeding was detected and selective angioembolization was warranted. The patient evolved with a perforated duo- denum and underwent laparotomy with exclusion of the pylorus and Roux-en-Y gastrojejunostomy. He was discharged nine days later. CONCLUSION: Intramural duodenal hematoma is a rare complication of pancreatitis. Selective emboliza- tion is the preferred treatment for hemorrhagic complications of pancreatitis. However, the risk of visceral ischemia and perforation should be considered.